2011
DOI: 10.1371/journal.pone.0023777
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Global Urban Land Expansion

Abstract: The conversion of Earth's land surface to urban uses is one of the most irreversible human impacts on the global biosphere. It drives the loss of farmland, affects local climate, fragments habitats, and threatens biodiversity. Here we present a meta-analysis of 326 studies that have used remotely sensed images to map urban land conversion. We report a worldwide observed increase in urban land area of 58,000 km2 from 1970 to 2000. India, China, and Africa have experienced the highest rates of urban land expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
1,040
9
37

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,776 publications
(1,113 citation statements)
references
References 17 publications
(20 reference statements)
27
1,040
9
37
Order By: Relevance
“…The consequences of urbanization are largely contingent on the size, location, and configuration of development (Weng, 2001;Zhou et al, 2004), with many environmental impacts exacerbated when new growth is expansive and/or fragmented in form (Alberti, 2005). A meta-analysis of urban expansion indicates that localto regional-scale studies are geographically biased, leaving even many large cities unstudied (Seto et al, 2011). Detailed maps on regional-to global-scale changes in urban land do not exist; previous efforts have been sample-based (Angel et al, 2005;Schneider & Woodcock, 2008), focused on one country (Homer et al, 2004;Wang et al, 2012), or drawn conclusions from datasets with substantial temporal and spatial mismatch and variability in how cities are defined (Seto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of urbanization are largely contingent on the size, location, and configuration of development (Weng, 2001;Zhou et al, 2004), with many environmental impacts exacerbated when new growth is expansive and/or fragmented in form (Alberti, 2005). A meta-analysis of urban expansion indicates that localto regional-scale studies are geographically biased, leaving even many large cities unstudied (Seto et al, 2011). Detailed maps on regional-to global-scale changes in urban land do not exist; previous efforts have been sample-based (Angel et al, 2005;Schneider & Woodcock, 2008), focused on one country (Homer et al, 2004;Wang et al, 2012), or drawn conclusions from datasets with substantial temporal and spatial mismatch and variability in how cities are defined (Seto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, its utilization has been greatly impeded due to cloud and cloud shadow contamination and inadequate algorithms to analyze them. Consequently, the vast majority of the applications are confined to individual small regions [13]. In terms of cloud cover, a Landsat scene (185 km by 185 km) could be in one of the three statuses: clear (no clouds in the scene), partially contaminated (with some clouds but part of the land can still be seen from space), or completely contaminated (with 100% cloud cover).…”
Section: Etm+ Ndvi Composingmentioning
confidence: 99%
“…In fact, it has been the main resource in mapping urban areas, especially since its availability to the public as of 2008 at no charge [12]. In a meta-analysis of global urban land expansion, Seto et al [13] reported a total of 326 studies that have used remotely sensed images, mainly from Landsat, to map urban land conversion scattered around the world up to the year 2000. Although Landsat has contributed significantly to the understanding of urban land cover and land use change, these efforts have largely focused on individual city or city-region studies, with few comparative or global-scale studies at the Landsat resolution [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences range from land cover change to climate impacts, habitat loss, or extinction of species. Additionally it influences transportation developments, energy demand, or the automobile market (Seto et al, 2011). The main drivers in Europe, mentioned by the European Environment Agency, are e.g.…”
Section: Introductionmentioning
confidence: 99%